Dynamics of marine bacterial biofouling communities after initial Alteromonas genovensis biofilm attachment to anti-fouling paint substrates. (November 2021) - Kim, Hyun-Jung; Park, Joon Sang; Lee, Taek-Kyun; Kang, Donhyug; Kang, Jung-Hoon; Shin, Kyoungsoon; Jung, Seung Won
Abstract: To determine how bacterial communities succeed after the initial attachment of the bacterial biofilm adhesion using 16S rDNA meta-barcoding in plates coated with copper-based anti-fouling (AF) and non-AF (control) coatings as well as ambient seawater, coated plates were submerged in a marine environment in situ. Alteromonas genovensis ( Gammaproteobacteria ) in AF coating and Pacificibacter sp. ( Alphaproteobacteria ) in the control plate were initially abundant. In the AF coating, the abundance of A . genovensis decreased rapidly, whereas that of genus Phaeobacter ( Alphaproteobacteria ), Serratia ( Gammaproteobacteria ) and Cupriavidus ( Betaproteobacteria ) increased. Bacterial community in the control plate had a strong connection to pathogenic Vibrio spp. associated with the growth of invertebrates. Therefore, in the in situ AF coating experiment, A . genovensis accumulation was initially and intensively increased, and the bacteria responded to chemical antagonism, induced the proliferation of specific biofilm bacteria and influenced the interactions and recruitment of additional bacterial communities. Graphical abstract: Unlabelled Image Highlights: A . genovensis exhibited intensive attachment to AF coating in the early stage. P . marinus counts on the control plate were abundant in the early stage. A selective habitat was provided by the A . genovensis biofilm. The biofilm both stimulated and suppressed the growth of other bacteria. The biofilm provided a habitat for potentially pathogenic bacteria.